The relationship between self-esteem, pro-active personality and social support on career adaptability among undergraduate students - Fawehinmi, Olawole Olanre (2016)
Career adaptability refers to the flexible attribute of individuals toward their career endeavor in the face of volatile circumstances. As Malaysia is reaching its goal to achieve an industrialized nation status by 2020 and the increase in ageing population in 2030, there is a need to have a workforce that possess a high level of career adaptability in order to boost workforce efficiency. This can be achieved by having graduates that are highly intellectual, positive work-attitude, spontaneous and flexible to keep abreast with relevant and current skills and technical knowhow in the prevailing labour market in the country. The current level of shortage of required skills and attributes by fresh graduates in the country is alarming, thus drastic measures need to be taken by all stake holders, including the Human resource professionals, career counsellors, lecturers, government and the family institution. This study is to assess the level of career adaptability among undergraduate students by determining the relationship between career adaptability and self-esteem, proactive personality and social support among undergraduate students in public universities in Malaysia. Data was obtained from 188 questionnaires targeting undergraduate final year students of Bachelor of Business administration (BBA) taking the seminar course in Universiti Utara Malaysia, Kedah. The result analyzed with Statistical Package for the Social Sciences (SPSS) indicates a positive and significant correlation between pro-active personality and social support with the career adaptability level among the undergraduate students; with pro-active personality having the strongest significant positive relationship. It is noteworthy to mention that self-esteem did not indicate a significant relationship with career adaptability, because of the lack of mediating factor such as career exploration. It is recommended that there is a need to form a synergy among career counsellors, human professionals, lecturers and family members in order to boost the career adaptability of these students. This will enable the students to attain the necessary soft skills such as communication, decision making, critical thinking, interpersonal skill and English language proficiency. These skills are highly required in today`s competitive and volatile labour market, so that they can have a smooth school to work transition in the nearest future.